Chlamydia screening for pregnant women aged 16–25 years attending an antenatal service: a cost‐effectiveness study. (26th August 2015) - Ong, JJ; Chen, M; Hocking, J; Fairley, CK; Carter, R; Bulfone, L; Hsueh, A
Abstract : Objective: Determine the cost‐effectiveness of screening all pregnant women aged 16–25 years for chlamydia compared with selective screening or no screening. Design: Cost effectiveness based on a decision model. Setting: Antenatal clinics in Australia. Sample: Pregnant women, aged 16–25 years. Methods: Using clinical data from a previous study, and outcomes data from the literature, we modelled the short‐term perinatal (12‐month time horizon) incremental direct costs and outcomes from a government (as the primary third‐party funder) perspective for chlamydia screening. Costs were derived from the Medicare Benefits Schedule, Pharmaceutical Benefits Scheme, and average cost‐weights reported for hospitalisations classified according to the Australian refined diagnosis‐related groups. Main outcome measures: Direct costs of screening and managing chlamydia complications, number of chlamydia cases detected and treated, and the incremental cost‐effectiveness ratios were estimated and subjected to sensitivity analyses. Results: Assuming a chlamydia prevalence rate of 3%, screening all antenatal women aged 16–25 years at their first antenatal visit compared with no screening was $34, 931 per quality‐adjusted life‐years gained. Screening all women could result in cost savings when chlamydia prevalence was higher than 11%. The incremental cost‐effectiveness ratios were most sensitive to the assumed prevalence of chlamydia, the probability of pelvic inflammatory disease, the utility weight of a positive chlamydia test and the cost of the chlamydia test and doctor's appointment. Conclusion: From an Australian government perspective, chlamydia screening of all women aged 16–25 years old during one antenatal visit was likely to be cost‐effective compared with no screening or selective screening, especially with increasing chlamydia prevalence. Tweetable abstract: Chlamydia screening for all pregnant women aged 16–25 years during an antenatal visit is cost effective. Tweetable abstract: Chlamydia screening for all pregnant women aged 16–25 years during an antenatal visit is cost effective.